2012
DOI: 10.1039/c2ay25553g
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anionic impurities in hexafluorosilicic acid by capillary zone electrophoresis

Abstract: This paper reports an alternative analytical methodology for the determination of chloride and sulphate impurities in hexafluorosilicic acid, FSA, using capillary zone electrophoresis. The influence of different electrophoretic and matrix variables on electrophoretic response was studied. Samples were injected hydrodynamically onto a fused silica capillary of 63.5 cm  75 mm id, with an effective length of 55 cm. The capillary temperature was kept constant at 25 AE 1 C throughout the experiments. A voltage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The IC method also offers advantages compared to the capillary electrophoretic method previously applied to this matrixes (Ayarza et al 2012). The LOQs are lower than those obtained by CE, have higher sample throughput, and problems with capillary life are avoided.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The IC method also offers advantages compared to the capillary electrophoretic method previously applied to this matrixes (Ayarza et al 2012). The LOQs are lower than those obtained by CE, have higher sample throughput, and problems with capillary life are avoided.…”
Section: Discussionmentioning
confidence: 98%
“…A capillary zone electrophoresis method has been reported with an isotacophoresis initial step to determine anionic impurities on the silicon wafer surfaces treated with hydrofluoric acid vapor (Boden et al 1995). No references have been found dealing with the analysis of inorganic anionic impurities in fluorinated acids, apart from a previous study of our group (Ayarza et al 2012). In this previous study, the concentrations of chloride and sulfate were determined in hexafluorosilicic acid by capillary zone electrophoresis (CZE) with indirect photometric detection.…”
Section: Introductionmentioning
confidence: 97%
“…The type of feedstock and reactants used for the FSA production led to the formation of different secondary products that could persist as traces in FSA-derived SiO 2 . Ayarza et al [ 160 ] reported a new method for identifying impurities present in FSA implementing capillary zone electrophoresis, a method that could be applied at an industrial scale due to its simplicity and accuracy. In this study, the authors quantified as principal impurities the presence of chlorides and sulfates (both at a concentration of approx.…”
Section: Silica From Industrial Production Waste or End-of-life Productsmentioning
confidence: 99%